Prevention of Unhealthy Weight, Disordered Eating, and Poor Body Image in Children. Perspectives From Norwegian Parents and Healthcare Professionals - Fiskum, Charlotte; Riiber, Åshild; Eik-Nes, Trine Tetlie (Frontiers in Psychiatry, 2022)
Childhood obesity (ChO) and eating disorders are on the rise, with concerning effects on health. Early prevention is essential as interventions after problems arise are costly and with a low success rate. In Norway, prevention of ChO has been largely weight-centered, without desired effects. Confident Body, Confident Child (CBCC) is a universal program aimed at preventing ChO, disturbed eating, and body image problems through a health-centered intervention for parents of children between 2-6 years. The current study is part of a cultural adaptation and translation of CBCC into Norwegian. Method: Focus groups with parents (n = 16) and professionals (n = 11) were held around healthy eating, activity, and body image, with an emphasis on possible barriers for prevention as well as approaches considered helpful. The interviews were analyzed using interpretative phenomenological analysis. Results: Parents and professionals described parental stress connected to high standards, conflicting information, and parental comparison. A narrowing sense of normality around healthy living was described with little flexibility resulting in “all-or-nothing” thinking. Parents were anxious to say or do the wrong thing when regulating children’s food intake and when faced with comments about appearance. Parents and professionals described parental concern around children not eating enough, and professionals described an increase in parents using food as regulation. Both parents and professionals expressed that having a child with overweight was tied to a sense of failure and shame. Interventions related to overweight seemed to increase stress and shame, further complicating follow-up. As an alternative, parents and professionals expressed a desire for interventions with normalizing information around “good-enough” parenting related to food and weight. Discussion: The described fear of doing something wrong and lack of flexibility is interpreted within a stress-sensitive understanding, where stress and shame can influence parents towards mobilizing action or disengagement, presenting as dichotomous behaviors of “all-or-nothing”. Conclusion: Interventions that can normalize parental concerns in a non-moralizing way may reduce stress and shame. CBCC addresses all the major concerns raised in this study, providing parents with evidence-based information they can implement into everyday life. The Norwegian cultural adaptation added extra emphasis on normalization and shame-reduction.